HIV positive patient with GBS-like syndrome. (1st September 2017) - Shepherd, Samantha J.; Black, Heather; Thomson, Emma C.; Gunson, Rory N.
Abstract : Introduction. Guillain–Barré Syndrome (GBS) is an acute demyelinating polyneuropathy which can occur post-infection. Criteria of diagnosis of GBS include areflexia with progressive bilateral weakness in arms and legs. GBS can lead to severe respiratory and cardiac complications. The fatality rate can be up to 5 % in patients, depending on the severity of the symptoms. HIV can cause a range of neurological disorders including, on rare occasions, GBS. GBS can occur at any stage of HIV infection, highlighting the complexity of diagnosis of GBS within HIV patients. Case presentation. A 57 year old female with lumbar back pain radiating to the legs, poor mobility and tiredness, with reports of a viral-like illness four days previously, was initially diagnosed with a lower respiratory tract infection and discharged. Seventeen days later the patient was readmitted to hospital with progressive lower and upper limb weakness, areflexia and sensory loss. She was diagnosed with GBS and was unexpectedly discovered to be HIV-positive. HIV avidity was low indicating a recently acquired HIV infection. The patient was treated with intravenous immunoglobulin for five days for the GBS and commenced antriretrovirals for HIV. The patient was discharge from hospital 53 days after admission with walking aids and regular physiotherapy follow-up. Conclusion. This case highlighted the need for all clinicians to be aware that patients with symptoms of GBS, regardless of clinical history should be offered an HIV test. GBS can be the first sign a patient is HIV-positive.